A colorless, transparent and mechanically robust polyurethane elastomer: synthesis, chemical resistance and adhesive properties. (17th February 2022) - Zhang, Huijuan; An, Li; Wang, Xue; Niu, Chao; Hou, Xinjuan
Abstract : In this work, a transparent, mechanically strong and chemically resistant XDI-PUE adhesive was fabricated, which exhibited a remarkable tensile stress of 21.0 MPa with a break strain of 1608%. XDI-PUE also showed good chemical resistance towards toluene and NaOH aqueous solution. Abstract : A colorless and transparent polyurethane elastomer (PUE) with high mechanical strength, excellent adhesive performance and chemical resistance is highly desirable in applications such as advanced protecting films. It is still challenging to fabricate a PUE with outstanding transparency, high-strength, good chemical resistance and adhesion strength. In this work, a PUE was designed with polytetramethylene ether glycol (PTMEG) as the soft segment and aliphatic isocyanate ( m -xylylene diisocyanate, XDI) and 1, 6-hexanediol (HDO) as the hard segment. The resulting XDI-PUE showed a remarkable mechanical strength of 21.0 MPa with an elongation at break of 1608%. Owing to the amorphous phase structure and XDI chemical structure, the resulting PUE was highly transparent with ∼90% transparency. Moreover, the elastomer showed good chemical resistance toward organic and inorganic solvents, i.e., toluene and NaOH aqueous solution. After being immersed in toluene and 30% NaOH aqueous solution for 24 h, the mechanical strength of XDI-PUE can maintain 70% and 50% of the original tensile strength with the shape remaining unchanged. It is worth noting that XDI-PUE can adhere strongly to metal substrates like copper and aluminum, and the tensile shear strengths to copper and aluminum were 607 and 343 kPa, respectively. Molecular simulations confirmed the adhesion results and provided the optimized complexes of Cu and Al binding with XDI-PUE. The present study can provide an effective method for fabricating advanced flexible protecting films as well as give molecular insights into the adhesion mechanism of PUE and metals.